Autophagy Involved in Antiviral Activity of Sodium Tanshinone IIA Sulfonate against Porcine Reproductive and Respiratory Syndrome virus Infection in vitro. Issue 1 (January 2019) - Sun, Na; Sun, Panpan; Yao, Mingjie; Khan, Ajab; Sun, Yaogui; Fan, Kuohai; Yin, Wei; Li, Hongquan
Background: In previous research, we have demonstrated that sodium tanshinone IIA sulfonate (STS) has anti-porcine reproductive and respiratory syndrome virus (PRRSV) activity, but whether autophagy is involved in this process is still unknown. In this study, the autophagy effect of STS against PRRSV infection was investigated in vitro . Methods: Quantitative real-time PCR (qRT-PCR) and western blot was used to evaluate the inhibition ability of STS on the mRNA expression levels on cell autophagy genes, that is Beclin1, ATG5 and ATG7. Simultaneously, the effect of STS on N protein/gene expression was assessed by indirect immuno-fluorescence assay (IFA), qRT-PCR and western blot. Results: The results indicated that STS inhibits autophagy induced by PRRSV. In addition, STS effectively suppresses PRRSV's N protein replication and N gene expression in Marc-145 cells infected with PRRSV in a time-dependent manner. Conclusions: Our results suggest that STS exhibits anti-PRRSV activity in vitro by suppressing autophagy-related genes, which may provide a theoretical basis for further pharmacological agent development regarding PRRSV infection.